Writing faith and telling tales : literature, politics, and religion in the work of Thomas More - Betteridge, Thomas (Notre Dame, Indiana : University of Notre Dame Press, 2013)
Betteridge discusses Thomas More's writings in a broad cultural and chronological context and argues for a revision of existing legacies of More.
Politics -- Reason -- Heresy -- Devotion.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: More, Thomas, -- Saint, -- 1478-1535 -- Political and social views; More, Thomas, -- Saint, -- 1478-1535; Reformation -- England -- Historiography; Christian literature, Latin (Medieval and modern) -- England -- History and criticism; Great Britain -- History -- Henry VIII, 1509-1547.; Religious thought -- 16th century; Philosophy, Medieval; Humanism -- England -- History -- 16th century; England -- Intellectual life -- 16th century; Littérature chrétienne latine médiévale et moderne -- Angleterre -- Histoire et critique; Grande-Bretagne -- Histoire -- 1509-1547 (Henri VIII); Pensée religieuse -- 16e siècle.; Philosophie médiévale.; Humanisme -- Angleterre -- Histoire -- 16e siècle.; Angleterre -- Vie intellectuelle -- 16e siècle.; HISTORY / Modern / 16th Century; Christian literature, Latin (Medieval and modern); Humanism; Intellectual life; Philosophy, Medieval; Political and social views; Reformation -- Historiography; Religious thought; England; Great Britain; 1500-1599; Electronic books; Criticism, interpretation, etc; History